Health education in Swedish schools - what's on offer? - Varea, V.; Caldeborg, A.; Barker, D.; Quennerstedt, M. (Scandinavian journal of educational research, 2025)
The aim of this paper is to identify the dominant discourses of health and wellbeing that are offered in health education in Swedish schools. Issues of health and wellbeing are covered mainly in four school subjects in Sweden: physical education and health, home and consumer studies, biology, and social studies, and therefore, we interviewed teachers from those subjects to generate data. Six interrelated health discourses were identified from the data. All discourses were, however, also embedded within a health discourse with a comprehensive description of health as physical, psychological and social wellbeing. Results suggest that schools offer a Western and White discourse of health and that some content is overemphasised, and some is missing in relation to other non-dominant discourses of health and wellbeing.